Studi Etnoparenting “Manjujai” Pola Pengasuhan Anak Berbasis Kearifan Lokal pada Keluarga Etnis Minangkabau Studi Kasus di Nagari Kasang Padang Pariaman - Wirdanengsih, Wirdanengsih; Wita, Gusmira (ETNOSIA : Jurnal Etnografi Indonesia, 2025)
Indonesia, with its diverse ethnicities, has a meaningful culture to support children's growth and development. This study will examine ethnoparenting of Minangkabau ethnic group, termed manjujai. A qualitative approach was used, conducted in Nagari Kasang, Batang Anai District, Padang Pariaman Regency, West Sumatra with data gathered from in-depth interviews with 20 informants, direct observation of interactions between children, parents, and extended family members. The findings reveal that manjujai serves as an effective medium for strengthening children’s character. This tradition is expressed in various forms such as chants, songs, and simple games that holistically stimulate children’s cognitive, motoric, emotional, and spiritual development. The Minangkabau's extended family system, which is based on a matrilineal structure, reinforces the effectiveness of manjujai by making early childhood caregiving a collective responsibility of the larger family network. Despite concerns about the tradition's potential extinction as a result of modernization, manjujai is still actively practiced in Nagari Kasang, demonstrating the community's social structure and collective awareness of the importance of cultural identity preservation. Thus, Minangkabau ethnoparenting in the manjujai tradition represents a sustainable caregiving practice that positively contributes to child development.